2019
DOI: 10.1002/chem.201904142
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐Carbonic Acid Revisited: Carbonic Acid Monomethyl Ester as a Solid and its Conformational Isomerism in the Gas Phase

Abstract: In this work, earlier studies reporting α‐H2CO3 are revised. The cryo‐technique pioneered by Hage, Hallbrucker, and Mayer (HHM) is adapted to supposedly prepare carbonic acid from KHCO3. In methanolic solution, methylation of the salt is found, which upon acidification transforms to the monomethyl ester of carbonic acid (CAME, HO‐CO‐OCH3). Infrared spectroscopy data both of the solid at 210 K and of the evaporated molecules trapped and isolated in argon matrix at 10 K are presented. The interpretation of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
(160 reference statements)
0
12
0
Order By: Relevance
“…However, at 10−20 K, solid H 2 CO 3 can also be formed through reactions 5−7 involving newly formed CO ice that does not desorb from the ice at temperatures below 30 K (Acharyya et al 2007). As pointed out by Oba et al (2010), this reaction pathway leads to the formation of a different form of H 2 CO 3 , namely the γ-polymorph (Köck et al 2020). The H 2 CO 3 synthesized at 20 K in our experiments is likely a combination of βand γ-polymorph ice.…”
Section: Formation Of Pure H 2 Co 3 Icementioning
confidence: 97%
See 2 more Smart Citations
“…However, at 10−20 K, solid H 2 CO 3 can also be formed through reactions 5−7 involving newly formed CO ice that does not desorb from the ice at temperatures below 30 K (Acharyya et al 2007). As pointed out by Oba et al (2010), this reaction pathway leads to the formation of a different form of H 2 CO 3 , namely the γ-polymorph (Köck et al 2020). The H 2 CO 3 synthesized at 20 K in our experiments is likely a combination of βand γ-polymorph ice.…”
Section: Formation Of Pure H 2 Co 3 Icementioning
confidence: 97%
“…α-H 2 CO 3 presents weaker absorption bands in the O-H stretch regions than β-H 2 CO 3 , which has its strongest absorption band around 2600 cm −1 . However, more recently, the synthesis of α-H 2 CO 3 in methanolic solutions was reassigned to the monomethyl ester of carbonic acid (CAME, HO-CO-OCH 3 , Reisenauer et al 2014;Köck et al 2020), leaving the β-polymorph as the only confirmed form of H 2 CO 3 to date. It is known that H 2 CO 3 synthesized through energetic irradiation of CO 2 :H 2 O ice mixtures produces amorphous β-H 2 CO 3 that crystallises if heated to temperatures above 220 K (Hage et al 1995(Hage et al , 1996bBernard et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9−11 However, recent work with more advanced experimental techniques has shown that αcarbonic acid is actually the monomethyl ester of carbonic acid and is not a polymorph negating the need for any further analysis of the α phase. 12 Even so, efforts to describe βcarbonic acid computationally have been successful in correlating with experiments for infrared and Raman spectra of a linear octamer. 13 Attempts to construct a crystal structure through molecular dynamic methods suggest that the crystals with "sheet-like hydrogen bonding topologies" are among the most stable.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We performed infrared spectroscopy measurements of mixtures of gases in frozen neon matrixes, i.e., matrix-isolation infrared (MI-IR) spectroscopy. Former studies 17 , 18 have shown that the composition of an atmosphere trapped in a frozen matrix resembles the gas phase composition. Thus, MI-IR spectroscopy is a suitable analytical technique for investigating short-lived and unstable species from the gas phase.…”
Section: Experimental Methodology and Computational Detailsmentioning
confidence: 99%